Aging, Vulnerability and Managing Type 2 Diabetes During a Pandemic - McConatha, Jasmin Tahmaseb (Advances in Social Sciences Research Journal, 2020)
Older men and women have been found to be more vulnerable to negative outcomes should they contract Covid19, particularly if they also have comorbid conditions such as type 2 diabetes. Cultural, racial, ethnic, and social class differences exist in vulnerability to Covid19 and in the prevalence of type 2 diabetes. In the United States, for example, diabetes rates for minority and immigrant populations are higher than for non-Hispanic whites. During the a social health crisis, it is helpful to explore the ways that illness management and associated vulnerability influences the ways that minority elders attempt to maintain and promote their well-being. This paper presents a case study example of an older immigrant woman, diagnosed with type 2 diabetes, and her struggle to manage her illness during a pandemic. The risk of developing diabetes in the United States is 3 to 1 and risks increase with age (American Diabetes Association, 2020). Almost 50 % of black women as well as Hispanic men and women will develop diabetes in their lifetime (CDC, 2019). Disparities such as these have their origin in intersecting risk factors such as health care and lifestyle factors such as tress, poverty, weight, diet, and exercise patterns. Being a member of an ethnic minority and being overweight are the two significant factors associated with the onset of type 2 diabetes. During the coronavirus epidemic, these same factors also increase the risk for infection and for greater complications, even death as a result of infection (Society for Women’s Health Research, 2020). This essay illustrates the increased vulnerability and challenges including loneliness facing older women with type 2 diabetes during pandemic isolation.